Development and validation of Chronic Kidney Disease Knowledge, Attitude, and Practices (CKD-KAP) questionnaire - Tariq, Muhammad Haseeb; Sulaiman, Syed Azhar Syed; Farrukh, Muhammad Junaid; Goh, Khang Wen; Ming, Long Chiau (Frontiers in Medicine, 2022)
Background: Chronic Kidney Disease (CKD) is a complex condition leading to loss of kidney function. The objective of this study was to develop and validate a Knowledge, Attitude and Practice questionnaire on CKD (CKD-KAP) among practicing physicians in Pakistan since no validated tool was available for the said purpose. Methods: The study consisted of 4 phases with phase-I focusing on literature review, phase-II was the actual questionnaire development phase, face and content validity was determined in phase-III and finally pilot testing was performed in phase-IV to determine validity and reliability. The development phase encompassed thorough review of literature, focus-group discussion, expert review and evaluation. The validation phase consisted of content validity, face validity, construct validity, convergent validity and reliability. The pilot testing was performed by studying the KAP of 100 practicing physicians in tertiary care hospitals in Pakistan. The knowledge section of the validation phase utilized item response theory (IRT) analysis. The attitude and practices sections utilized exploratory factor analysis (EFA) theory. The reliability analysis utilized Cronbach’s alpha and correlations. Results: The CKD-KAP questionnaire had 3 main sections: knowledge, attitude, and practice. During the validation, IRT analysis was performed on knowledge, which focused on measure of the coefficient of discrimination and difficulty of the items. 40 out of 41 knowledge items have both discrimination and difficulty coefficients within acceptable range. The EFA model was also fitted in attitude and practices section and scree plot and Eigenvalues suggested 3 and 4 dimensions within the attitude and practices section. The factor loading of all items was found to be acceptable except one item in attitude which was deleted. The convergent validity demonstrated significant association between all three section except knowledge and practices. The reliability (internal consistency) analysis demonstrated Cronbach’s alpha values above 0.7 and significant inter-item correlation. The final model of CKD-KAP had 40 knowledge, 13 attitude and 10 practices items with a combination of both positive as well as negative statements. Conclusions: The CKD-KAP was found to be psychometrically valid and reliable, hence can be used to determine the knowledge, attitude and practices of physicians towards chronic kidney disease.